La cabalgata montubia y turismo cultural en el cantón Baba, Provincia de Los Ríos - Muñoz Moyano, Estefani Gabriela (2022)
The present case study is directed to the Montubia Parade and Cultural Tourism, the objective of this research is to identify the Montubia Parade to strengthen Cultural Tourism in the Baba canton, this being a scheduled event where cultural recreational activities of identity are carried out. Culture of a people. Cultural Tourism is a type of tourist activity that is focused on prevailing the sense of belonging of a people and its importance also remains in consumption trends due to the offer of attractions and cultural events, which are responsible for disseminating and transmitting the main knowledge cultures created by man being part of their cultural identity. For the development and fulfillment of this research work, information is collected through an online survey and different investigative methods with the aim of obtaining information to achieve the goal set out in this research project, resulting in the implementation of Cultural Tourism contributing to growth. Socioeconomic of Baba Canton.